Dose-Effect of Zearalenone on the Localization and Expression of Growth Hormone, Growth Hormone Receptor, and Heat Shock Protein 70 in the Ovaries of Post-weaning Gilts - Song, Tingting; Liu, Xiufeng; Yuan, Xuejun; Yang, Weiren; Liu, Faxiao; Hou, Yanmeng; Huang, Libo; Jiang, Shuzhen (Frontiers in Veterinary Science, 2021)
Zearalenone (ZEA) has an estrogen-like effect, which can injure the reproductive system of animals, causing infertility and abortion in sows. However, the underlying mechanisms are still not clear. The objective of this study was to assess the effects of ZEA on the localization and expression of growth hormone (GH), growth hormone receptor (GHR), and heat shock protein 70 (Hsp70) in the ovaries of post-weaning gilts. Forty healthy post-weaning gilts were randomly provided one of four diets: normal basal diet supplemented with 0 (control), 0.5 (ZEA0.5), 1.0 (ZEA1.0), and 1.5 (ZEA1.5) mg ZEA / kg. Gilts were housed and fed individually for 35 days; the ovaries were collected after euthanasia for antioxidant index, relative mRNA and protein expression, and immunohistochemical analyses of GH, GHR, and Hsp70. The results revealed that glutathione peroxidase and total superoxide dismutase levels decreased (p < 0.05), whereas malondialdehyde level increased (p < 0.05) with increasing ZEA content. The localization pattern of GH, GHR, and Hsp70 in ZEA-treated gilts was the same as that in the control; however, the localization of yellow and brown immunoreactive substances of GH, GHR, and Hsp70 was stronger in the ZEA groups than in the control. The relative mRNA and protein expression of GHR and Hsp70 was the highest in the ZEA1.0 group (p < 0.05), whereas that of GH was the highest in the ZEA0.5 group (p < 0.05). The mRNA and protein expression of GH was lower in the ZEA1.5 group than in the control (p < 0.05). Hsp70 results showed adverse responses to increasing ZEA levels in gilt ovaries, suggesting that Hsp70 played an important role in alleviating ZEA-induced oxidative stress.